In vivo anti-tumor effect of PARP inhibition in IDH1/2 mutant MDS/AML resistant to targeted inhibitors of mutant IDH1/2 - Gbyli, Rana; Song, Yuanbin; Liu, Wei; Gao, Yimeng; Biancon, Giulia; Chandhok, Namrata S.; Wang, Xiaman; Fu, Xiaoying; Patel, Amisha; Sundaram, Ranjini; Tebaldi, Toma; Mamillapalli, Padmavathi; et al. (Leukemia, 2022)
Treatment options for patients with relapsed/refractory acute myeloid leukemia (AML) and myelodysplastic syndromes (MDS) are scarce. Recurring mutations, such as mutations in isocitrate dehydrogenase-1 and -2 (IDH1/2) are found in subsets of AML and MDS, are therapeutically targeted by mutant enzyme-specific small molecule inhibitors (IDH m i). IDH mutations induce diverse metabolic and epigenetic changes that drive malignant transformation. IDH m i alone are not curative and resistance commonly develops, underscoring the importance of alternate therapeutic options. We were first to report that IDH1/2 mutations induce a homologous recombination (HR) defect, which confers sensitivity to poly (ADP)-ribose polymerase inhibitors (PARPi). Here, we show that the PARPi olaparib is effective against primary patient-derived IDH1/2-mutant AML/ MDS xeno-grafts (PDXs). Olaparib efficiently reduced overall engraftment and leukemia-initiating cell frequency as evident in serial transplantation assays in IDH1/2-mutant but not -wildtype AML/MDS PDXs. Importantly, we show that olaparib is effective in both IDH m i-naïve and -resistant AML PDXs, critical given the high relapse and refractoriness rates to IDH m i. Our pre-clinical studies provide a strong rationale for the translation of PARP inhibition to patients with IDH1/2-mutant AML/ MDS, providing an additional line of therapy for patients who do not respond to or relapse after targeted mutant IDH inhibition.